The Implementation of Character Education Values to Prevent Radicalism at the Indonesia-Malaysia Border - Imran, Imran; Ramadhan, Iwan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
This study aimed to investigate the implementation of character education values as a means for preventing radicalism along the Indonesia-Malaysia border (specifically focusing on students at SMAN 1 or Public Senior High School 1, Jagoi Babang District, Bengkayang Regency). The study employed a descriptive study. The research focused on character education values as a means to prevent or suppress radicalism among the people of Jagoi Babang District, who were susceptible to ideas that contradicted the national ideology. The main targets of this effort were the students, who often played a role in provoking radical behavior. The study findings indicate that students were aware of their citizenship status due to their exposure to schooling. However, the availability of items from surrounding countries frequently encouraged students to consume a greater quantity of Malaysian products. Empirical evidence demonstrated that students had an innate comprehension of radicalism, despite the researcher merely hinting at the concept. Before being probed with more detailed inquiries during the interview, students were capable of offering comprehensive insights. The majority of students had exhibited their comprehension of the influence of radicalism. According to the research, schools in Jagoi Babang were not offering enough extracurricular, co-curricular, and in-school activities to keep students from becoming radicalized. This was true both inside the schools and in border communities. Nevertheless, students had prior knowledge regarding radicalism and its risks.